Clinical and prognostic insights into radiation-associated angiosarcoma: a multi-institutional analysis - Melissa Harbrücker; Sebastian Hoffmann; Johannes Tobias Thiel; Noelle Samira Jacob-Rehfeld; Sebastian M. Christ; Adrien Daigeler; Anna Duprée; Felix Ehret; Anne Flörcken; Peter Hohenberger; Bernd Kasper; Christoph Reißfelder; et al. (Radiation Oncology, 2026)
Abstract Purpose To evaluate oncological outcomes and prognostic factors in patients with radiation-associated angiosarcoma (RAAS) treated at referral centers. Methods We conducted a multi-institutional retrospective cohort study of patients with histopathologically confirmed primary or recurrent RAAS treated at four referral centers in Germany. Endpoints were overall survival (OS) and progression-free survival (PFS), estimated using the Kaplan–Meier method. Prognostic factors were assessed using multivariable Cox regression. Results Among 71 patients (97.2% female; median age 69 years), 90% had a history of breast cancer treated with radiotherapy (RT). RAAS developed after a mean latency of 7 years, with a median RT dose of 59.4 Gy. Over a median follow-up of 13.0 months, OS reached a median of 41.7 months, with 1- and 2-year rates of 82.9% and 61.7%, respectively. Median PFS was 9.5 months, with 1- and 2-year rates of 43.7% and 27.1%. Larger tumor size (HR 1.09, p = 0.032) and metastatic disease at diagnosis (HR 2.98, p = 0.003) were associated with worse OS. Conclusions RAAS are aggressive, frequently relapsing malignancies occurring years after RT. Larger tumor size and metastatic presentation are associated with worse OS. Multi-institutional and translational studies are needed to clarify disease biology, refine risk factors, and guide treatment strategies.